Quality Education Counts for Skills and Growth - World Bank (World Bank, Washington, DC, 2016)
The quality and relevance of education are paramount to achieve economic growth. International research shows that the subject matter learned and skillset developed in the classroom is the foundation for future success in the work place, and serves as a superior predictor of economic growth compared with the number of years of school. One recent study, using a database of comparable test scores for over 50 countries, finds that a single standard deviation difference in tests scores between countries equates to roughly 2 percentage points in annual long-term Gross Domestic Product (GDP) growth. These findings hold true across high-income, middle-income, and low-income countries and all geographical regions. Despite significant investments in formal education, economic growth in the region has slowed in recent years and there is a need for improved labor productivity.